Enhanced solid phase extraction of DNA using hydrophilic monodisperse poly(methacrylic acid-co-ethylene dimethacrylate) microparticles - Šálek, Petr; Filipová, Marcela; Horák, Daniel; Proks, Vladimír; Janoušková, Olga (Molecular biology reports, 2019)
The efficiency of solid phase extraction (SPE) of DNA on polymer particles is limited by the features of the applied solid support, such as size, hydrophilicity, and functionality and their application in SPE also requires additional steps and compounds to finally obtain sufficient amount of high-quality DNA. The present study describes a preparation of sub-micrometer monodisperse poly(methacrylic acid-co-ethylene dimethacrylate) (PME) particles by precipitation polymerization. The effect of the ethylene dimethacrylate (EDMA) crosslinker concentration on morphology and particle size, which varied from 730 to 900 nm, was investigated. The particles with 5 and 15 wt% EDMA were selected for a study of SPE of plasmid DNA under various adsorption and elution conditions, followed by the enzymatic restriction of isolated DNA to verify a quality the nucleic acid. The particles with 15 wt% EDMA were suitable for the SPE because they retained better colloidal stability during the adsorption without additional induction of DNA conformational change. The quality of isolated DNA was finally verified by enzymatic restriction by restriction endonuclease EcoRI. Moreover, the developed method using PME particles was successfully utilized for DNA isolation from Escherichia coli lysate.
Keywords: Solid Phase Extraction; velikost částic; EcoRI; Hydrogen-Ion Concentration; DNA bakterií; Particle Size; Microparticles; polymethylmethakrylát; DNA, Bacterial; Polymers; DNA; Polymethyl Methacrylate; Solid phase extraction; polymery; extrakce na pevné fázi; Poly(methacrylic acid-co-ethylene dimethacrylate); Enzymatic restriction; koncentrace vodíkových iontů; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions